2013
DOI: 10.1073/pnas.1314755110
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of ATG3 recognition by the autophagic ubiquitin-like protein ATG12

Abstract: The autophagic ubiquitin-like protein (ublp) autophagy-related (ATG) 12 is a component of the ATG12∼ATG5-ATG16L1 E3 complex that promotes lipid conjugation of members of the LC3 ublp family. A role of ATG12 in the E3 complex is to recruit the E2 enzyme ATG3. Here we report the identification of the ATG12 binding sequence in the flexible region of human ATG3 and the crystal structure of the minimal E3 complexed with the identified binding fragment of ATG3. The structure shows that 13 residues of the ATG3 fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
107
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(110 citation statements)
references
References 29 publications
3
107
0
Order By: Relevance
“…This interaction is critical for E2-E3 complex formation. 169,170 In addition, the N-terminal 20 amino acids of mouse and human ATG3 form a membrane curvaturesensing amphipathic helix that allows LC3/GABARAP lipidation to proceed efficiently. 171 Finally, the N-terminal domain of ATG16L1 is responsible for the localization of the ATG12-ATG5 conjugate to membranes during autophagosome formation.…”
Section: Lipidation Of Atg/atg Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…This interaction is critical for E2-E3 complex formation. 169,170 In addition, the N-terminal 20 amino acids of mouse and human ATG3 form a membrane curvaturesensing amphipathic helix that allows LC3/GABARAP lipidation to proceed efficiently. 171 Finally, the N-terminal domain of ATG16L1 is responsible for the localization of the ATG12-ATG5 conjugate to membranes during autophagosome formation.…”
Section: Lipidation Of Atg/atg Proteinsmentioning
confidence: 99%
“…171 Finally, the N-terminal domain of ATG16L1 is responsible for the localization of the ATG12-ATG5 conjugate to membranes during autophagosome formation. 168,170 Proteolysis of Atg/ATG Proteins Some proteins are activated by proteolysis following translation because they are synthesized as inactive precursors, and proteolysis is involved in several different stages of autophagy. In the initiation phase of autophagy, Atg8 and its orthologs are synthesized as inactive precursors, which are then activated through removal of a C-terminal polypeptide segment.…”
Section: Lipidation Of Atg/atg Proteinsmentioning
confidence: 99%
“…We previously showed that the FR is important for the interaction with E3 in humans and demonstrated that a short region of human ATG3 FR interacts with ATG12 of E3 (termed the region that interacts with ATG12; RIA12) [18]. On the basis of our structural and biochemical characterizations of this interaction, we proposed that the RIA12 is a novel binding motif for ATG12, another ubiquitin-like protein in autophagy, and is required for recruitment of ATG3 by E3 [18]. Another previous study showed that binding of ATG3 to the E1 and E3 are mutually exclusive due to the overlapping E1 and E3 binding sites within the FR [19].…”
Section: Introductionmentioning
confidence: 99%
“…The details of Atg3 interaction with the membrane lipid matrix are, to our knowledge, virtually unexplored. Due to the ability of Atg3 to interact with Atg12 17,18 , Atg12-Atg5-Atg16L1 would promote a more efficient recruitment of Atg3 to membranes in vivo 19,20 . Atg12-Atg5 induces a reorientation of Atg3 catalytic cysteine toward a threonine residue so that Atg3 conjugase activity is stimulated 13,21 .…”
mentioning
confidence: 99%